Muscle-Inspired Anisotropic Aramid Nanofibers Aerogel Exhibiting High-Efficiency Thermoelectric Conversion and Precise Temperature Monitoring for Firefighting Clothing - Yu, Zhicai; Wan, Yuhang; Zhou, Mi; Mia, Md Hasib; Huo, Siqi; Huang, Lele; Xu, Jie; Jiang, Qing; Zheng, Zhenrong; Hu, Xiaodong; He, Hualing (Nano-Micro Letters, 2025)
Enhancing the firefighting protective clothing with exceptional thermal barrier and temperature sensing functions to ensure high fire safety for firefighters has long been anticipated, but it remains a major challenge. Herein, inspired by the human muscle, an anisotropic fire safety aerogel (ACMCA) with precise self-actuated temperature monitoring performance is developed by combining aramid nanofibers with eicosane/MXene to form an anisotropically oriented conductive network. By combining the two synergies of the negative temperature-dependent thermal conductive eicosane, which induces a high-temperature differential, and directionally ordered MXene that establishes a conductive network along the directional freezing direction. The resultant ACMCA exhibited remarkable thermoelectric properties, with S values reaching 46.78 μV K−1 and κ values as low as 0.048 W m−1 K−1 at room temperature. Moreover, the prepared anisotropic aerogel ACMCA exhibited electrical responsiveness to temperature variations, facilitating its application in intelligent temperature monitoring systems. The designed anisotropic aerogel ACMCA could be incorporated into the firefighting clothing as a thermal barrier layer, demonstrating a wide temperature sensing range (50–400 °C) and a rapid response time for early high-temperature alerts ( 1.43 s). This work provides novel insights into the design and application of temperature-sensitive anisotropic aramid nanofibers aerogel in firefighting clothing. Highlights: 1 Muscle-inspired anisotropic aramid nanofibers thermoelectric aerogel was prepared via directional freeze-drying strategy. 2 Resultant anisotropic aerogel exhibited high-efficiency thermoelectric conversion with Seebeck coefficient of 46.78 μV K−1 and low thermal conductivity of 0.048 W m−1 K−1. 3 Thermoelectric aerogel-based multistage wireless high-temperature alarm system achieves a wide temperature sensing range (50–400 °C) and sensitivity response time (trigger time 1.43 s) for firefighting clothing.